Accessing Difluoromethylated and Trifluoromethylated cis‐Cycloalkanes and Saturated Heterocycles: Preferential Hydrogen Addition to the Substitution Sites for Dearomatization. Issue 47 (8th October 2019) - Zhang, Xue; Ling, Liang; Luo, Meiming; Zeng, Xiaoming
Abstract: Reported here is a straightforward process in which a cyclic (alkyl)(amino)carbene/Rh catalyst system facilitates the preferential addition of hydrogen to the substitution sites of difluoromethylated and trifluoromethylated arenes and heteroarenes, leading to dearomative reduction. This strategy enables the diastereoselective synthesis of cis ‐difluoromethylated and cis ‐trifluoromethylated cycloalkanes and saturated heterocycles, and even allows formation of all‐ cis multi‐trifluoromethylated cyclic products with a defined equatorial orientation of the di‐ and trifluoromethyl groups. Deuterium‐labeling studies indicate that hydrogen preferentially attacks the substitution sites of planar arenes, resulting in dearomatization, possibly with heterogeneous Rh as the reactive species, followed by either reversible or irreversible hydrogen addition to the nonsubstitution sites. Abstract : Add‐ons : The preferential addition of hydrogen to the substitution sites of difluoromethylated and trifluoromethylated arenes and heteroarenes for dearomative reduction is described. This strategy enables the rapid and diastereoselective synthesis of cis ‐difluoromethylated and cis ‐trifluoromethylated cycloalkanes and saturated heterocycles, as well as the construction of all‐ cis multiply trifluoromethylated cyclic aliphatic compounds with a defined equatorial orientation of the di‐ and trifluoromethyl groups.